Penerapan LKPD Inkuiri Terstruktur Berbantuan Quick Response Code untuk Meningkatkan Keterampilan Proses Sains Peserta Didik Kelas VII SMPN 18 Makassar - R.A Athifah Radhiyyah Ulfah; Muhammad Aqil Rusli; Salma Samputri (Celebes Science Education, 2025)
This study aims to determine 1) The level of Science Process Skills of VII grade students before and after the application of Structured Inquiry LKPD assisted by Quick Response Code, 2) Improvement of Science Process Skills of VII grade students after the application of Structured Inquiry LKPD assisted by Quick Response Code. This type of research is Pre-Experimental research with a research design using One Group Pretest-posttest Design. The population was all VII grade students of SMPN 18 Makassar, school year 2022/2023 consisting of 10 classes with a total of 351 people, the sample was selected by purposive sampling and VII 2 class totaling 21 people was selected as the sample. The research instrument was a science process skills test question. Data collection was done by giving Pretest and Posttest. Data were analyzed with descriptive statistics and inferential statistics. Based on the research results obtained 1) The level of science process skills of students before the application of structured inquiry LKPD assisted by Quick Response Code is in the medium category with an average pretest score of 9.04. The level of science process skills of students after the application of structured inquiry LKPD assisted by Quick Response Code is in the high category with an average posttest score of 12.1, 2) The improvement of students' science process skills after the application of structured inquiry LKPD assisted by Quick Response Code is in the medium category with N-Gain 0.3, 3) The application of structured inquiry LKPD assisted by Quick Response Code can improve the science process skills of VII grade students of SMP Negeri 18 Makassar, this is evidenced by the t test obtained t count = 25.08> t table = 2.085.